LB03.08: HYPERTENSION RELATED VARIANT OF SOLUTE CARRIER FAMILY 39 MEMBER 8 GENE INFLUENCES CADMIUM UPTAKE AND CELL TOXICITY. (June 2015) - Zhang, R.; Witkowska, K.; Ng, F.; Caulfield, M.J.; Ye, S.
Abstract : Objective: hSLC39A8 (human solute carrier family 39 member 8) encodes a transmembrane protein that co-transports divalent heavy metal cations, such as Cd2+, with elusive physiological role. Recent genome-wide association studies have identified a non-synonymous single nucleotide polymorphism rs13107325 to be associated with hypertension. To investigate the functional impact of rs13107325 resulting in an amino acid substitution from Ala to Thr (A391T) in SLC39A8 on Cd2+ transport and the downstream signalling pathways. Design and method: Intracellular Cd2+ uptake was measured in HEK293 cells overexpressing SLC39A8 (Measure-iTTM Pb and Cd assay kit), and in human umbilical vascular endothelial cells (HUVECs) of different genotypes. Cd2+- and genotype-dependence of ERK1/2 and NF-kB pathway's activation were investigated by immunoblotting and dual-luciferase reporter assay. Cytotoxicity was measured by the lactate dehydrogenase assay and MTS assay. Molecular dynamics simulations were performed to predict in silico the effect of A391T on the structure and dynamics of SLC39A8 by using Robetta, TMHMM and etc. Results: Overexpression of Ala variant in HEK293 resulted in higher Cd2+ uptake and higher cytotoxicity as compared with the Thr variant. This is associated with increased phosphorylation of ERK1 and NF-kB activation. Similar trends were observed in HUVECs with endogenous SLC39A8. Bioinformatics tools also suggested a conformational change of the α-helical structural transition (residual 390–392) in the Thr mutant, which potentially attenuates the protein function. Conclusions: Increased Cd2+ uptake by SLC39A8 Ala variant (blood pressure raising allele) is associated with higher cell death in human kidney and endothelial cells. Therefore its altered function due to rs13107325 may indicate a potential therapeutic target in hypertension.